INVENTORY MANAGEMENT: A CASE STUDY AT A DEALERSHIP IN THE MUNICIPALITY OF ARACAJU/SE - Santos, Amanda de Jesus; de Souza, Heloísa Thais Rodrigues (Seven Editora, 2026)
Inventory management is fundamental to the operation of companies, especially in the automotive sector, which works with a wide variety of parts and high turnover. Poorly managed inventory can result in excess stock, obsolescence, lost sales due to lack of available products, and unnecessary storage costs. Given the above, the general objective of this work was to analyze the inventory management of an automotive dealership located in Aracaju/SE, and its specific objectives were: To map the stages of the inventory control process in the company; To identify problems related to inventory control; and To propose an action plan regarding the obstacles encountered, with proposals for improvements for the company. To this end, given the situation found in the company, the following question is posed: what are the main improvement actions for the company's inventory management? The research was developed through a case study, with a qualitative-quantitative approach, using direct observation, inventory analysis, and inventory count. During the analysis, problems related to inventory organization, lack of standardization, discrepancies between the system and the physical inventory, as well as failures in the receipt and storage of parts were identified. Based on this, tools such as flowcharts, ABC Curve, 5S, and 5W2H were applied, with the goal of improving the organization and control of inventory. The main improvements included the reorganization of parts, the standardization of locations, the creation of a suitable space for receiving and shipping, and the definition of a person responsible for the sector. The results showed improvements in organization, a reduction in errors, greater agility in processes, and increased reliability of inventory information. Thus, it is concluded that good inventory management directly contributes to the efficiency of the company and to improved customer service.